Elevated blood viscosity is associated with cerebral small vessel disease in patients with acute ischemic stroke. Issue 1 (December 2017) - Song, Seung; Kim, Jeong; Lee, Joon; Yun, Yeo-Min; Choi, Dong-Hee; Kim, Hahn
Abstract Background Increased level of blood viscosity, which is one of the major factors that determine blood rheology, has been reported as a risk factor or predictor for cerebrovascular events. We investigated how blood viscosity is associated with acute stroke and chronic radiological manifestations of cerebral small vessel disease, and how blood viscosity changes after stroke. Methods We prospectively enrolled consecutive patients with acute ischemic stroke. Whole blood viscosities at a low or high shear rate were measured using a scanning capillary tube viscometer, and were referred to as diastolic blood viscosity (DBV) and systolic blood viscosity (SBV), respectively. Correlations between blood viscosity and acute stroke etiology or chronic radiological manifestations of cerebral small vessel disease were investigated. The temporal profiles of blood viscosity at the onset of stroke and follow-up at 1 and 5 weeks were investigated. Results Of the 127 patients admitted with acute ischemic stroke, 63 patients were included in the final analyses. DBV at the onset of stroke was significantly higher in small artery occlusion (SAO) stroke than in other stroke subtypes (p = 0.037). DBV showed a significant positive correlation with the number of chronic lacunes (r = 0.274, p = 0.030). The temporal profiles of DBV in SAO stroke showed a transient decrease due to the hydration therapy after 1 week and recurrent elevation at 5 week follow-up (p = 0.009). Conclusions Our study suggests that elevated DBV may play a role in the development of acute and chronic manifestations of cerebral small vessel disease. The recurring elevation of DBV in SAO stroke indicates that sufficient hydration and additional therapeutic interventions targeting blood viscosity may be needed in patients with SAO stroke.